Determinants and Theoretical Perspectives of Stock Investment Decisions: A Systematic Review - Rifa Haenun Alya; Suhendi Suhendi; Muchamad Bachtiar (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Background: Stock investment decision-making is a complex process influenced not only by rational economic considerations but also by psychological, behavioral, and contextual factors. Although numerous studies have examined various determinants of investment decisions, the existing literature remains fragmented and lacks an integrated synthesis that systematically maps the key factors and theoretical frameworks influencing investor behavior. Purpose: This study aims to systematically identify, synthaResearch on stock investment decisions continues to evolve, yet existing findings remain scattered and address determining factors in isolation. This study aims to identify, map, and synthesize the factors that influence stock investment decisions. The method used is a Systematic Literature Review (SLR) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were obtained from the Scopus database, yielding 97 articles that met the inclusion criteria for analysis. The results indicate that stock investment decisions are influenced by six main dimensions: behavioral biases, financial literacy, psychological characteristics, external and contextual factors, demographic characteristics, and values and religiosity. The findings also suggest that the Behavioral Finance perspective dominates the literature in explaining investor behavior. The contribution of this study is the development of an integrated conceptual framework that unifies the various determinants of stock investment decisions, which were previously fragmented in the literature. The research results can serve as a foundation for the development of theory and further research on investment behavior.esize, and map the major determinants and theoretical perspectives influencing stock investment decisions by integrating findings from previous empirical studies. Design/methodology/approach: This study employs a Systematic Literature Review (SLR) based on the PRISMA framework. Literature was retrieved from the Scopus database using structured keyword queries, resulting in 97 peer-reviewed articles published between 2015 and 2026 included in the analysis. Findings/Result: The findings reveal that stock investment decisions are shaped by a complex interaction of multiple determinants. The review identifies six major dimensions that consistently influence investment decisions: behavioral biases, financial literacy and knowledge, psychological and personal traits, external and contextual factors, demographic variables, and values and religiosity. Among these, behavioral biases particularly overconfidence, herding behavior, and heuristic-driven decision-making emerge as dominant determinants. The results also highlight a growing research trend integrating digital and social influences, such as social media and online investor communities, into the analysis of investment behavior. Conclusion: The study concludes that stock investment decisions are multidimensional and context-dependent, extending beyond traditional rational financial models. Understanding the interaction between psychological, informational, and socio-cultural factors is essential for explaining investor behavior and improving the quality of investment decision-making in modern capital markets. Originality/value (State of the art): This study contributes to the literature by providing a comprehensive synthesis and conceptual mapping of determinants influencing stock investment decisions through a systematic review of recent research. By integrating behavioral, psychological, and contextual perspectives into a unified framework, this research offers a holistic understanding of investor behavior and highlights emerging research directions, particularly the role of digital ecosystems and social influences in shaping investment decisions.